Analisis Sistem Informasi Akuntansi Penggajian Pada Pt. Galang Insan Pratama - Lestari, Syahnaz Haq Murni; Nurmilah, Risma (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to describe the payroll accounting information system at PT. Galang Insan Pratama. This research took the object of research at PT. Galang Insan Pratama. Methods of data collection using observation, interviews and documentation. The data analysis technique used is a qualitative descriptive analysis technique by describing the payroll accounting information system that exists within the company including activities in the payroll system, documents used in the payroll system, accounting records used in the payroll system, functions related to the payroll system. payroll, the network of procedures that make up the system, the internal control system and the constraints contained in the payroll accounting information system. The results of this study indicate that the application of payroll accounting information systems at PT. Galang Insan Pratama in fulfilling the elements and objectives of internal control is still less effective. This is characterized by a computerized system that does not support, lack of supervision when fingerprints are tampered with, delays in submitting employee overtime work documents to the HRD staff and the presence of dual tasks in the payroll accounting information system.